## (3x^2)-(x)=1 Solve for x: If you could can you show steps

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

Lorem ipsum dolor sit amet, consectetur adipiscing elit.Morbi adipiscing gravdio, sit amet suscipit risus ultrices eu.Fusce viverra neque at purus laoreet consequa.Vivamus vulputate posuere nisl quis consequat.

## Answers ( No )

Answer:x = 0.787 and x = -0.565

Step-by-step explanation:Here’s how I got these answers:

(3x^2)-(x)=1 can be rewritten as the quadratic 9x^2 – x – 1 = 0. Here a = 9, b = -1 and c = -1. The discriminant b^2-4ac is therefore 1-4(9)(-1) = 37. There are two real, unequal roots (values of x that make the given equation true). They are:

-(-1) plus or minus √37

x = ————————————-

-9

Simplifying, we get:

x = (1 + √37)/9 and x = (1 – √37)/9

This results in x = 0.787 and x = -0.565